Fluctuation of Indian monsoon during the last glacial period revealed by pollen analysis of Kathmandu Basin sediments, Nepal Himalaya - Fujii, Rie; Sakai, Harutaka; Miyoshi, Norio (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 133-4